Determining the Causes of Internally Displaced Persons (IDPS) and Counselling for Social and Psychological Adjustment in Plateau State, Nigeria - Godfrey, R. Dungum; Tafida, M. Adjei (Kashere Journal of Education, 2022)
This study investigated the main causes of internally displaced persons (IDPs) and proffered counselling intervention for social and psychological adjustment in Plateau state. The survey research design was adopted for this study. A questionnaire was used to elicit information from sixty (60) respondents who were randomly selected from the three camps for the study. 13 factors were presented to the respondents as to determine the main factors that are responsible for internally displaced persons in Plateau State, Data were analyzed and results indicated that the main causes of Internally displaced people in Plateau State include: herdsmen/farmers’ conflicts, Boko Haram activities, Religious crises, Political conflict, Communal conflict, and disparity in political appointment. It was also found that the following factors are harmful and responsible for displacement of people from their homes in plateau state, which include: Security agents who cannot protect properties and harmless civilians, Natural disasters, and lack of employment. Based on the findings of this study, recommendations were made towards improving the enormous challenges arising from the internally displaced persons in Plateau state and Nigeria at large.